Indonesia’s 2022 Presidency for the G20 Summit in a Strategic Intelligence Perspective Anticipating Security and Hidden Agenda Issues - Sundawan SALYA; Yassar NANDANA (Indonesia Strategic Sustainability, 2022)
Indonesia is trusted to host the G20 summit in 2022. This opportunity is the first time since the G20 was established. With the slogan